Detection of SARS-CoV-2 within the healthcare environment: a multi-centre study conducted during the first wave of the COVID-19 outbreak in England. (February 2021) - Moore, G.; Rickard, H.; Stevenson, D.; Aranega-Bou, P.; Pitman, J.; Crook, A.; Davies, K.; Spencer, A.; Burton, C.; Easterbrook, L.; Love, H.E.; Summers, S.; et al.
Summary: Background: Understanding how severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is spread within the hospital setting is essential in order to protect staff, implement effective infection control measures, and prevent nosocomial transmission. Methods: The presence of SARS-CoV-2 in the air and on environmental surfaces around hospitalized patients, with and without respiratory symptoms, was investigated. Environmental sampling was undertaken within eight hospitals in England during the first wave of the coronavirus disease 2019 outbreak. Samples were analysed using reverse transcription polymerase chain reaction (PCR) and virus isolation assays. Findings: SARS-CoV-2 RNA was detected on 30 (8.9%) of 336 environmental surfaces. Cycle threshold values ranged from 28.8 to 39.1, equating to 2.2 x 10 5 to 59 genomic copies/swab. Concomitant bacterial counts were low, suggesting that the cleaning performed by nursing and domestic staff across all eight hospitals was effective. SARS-CoV-2 RNA was detected in four of 55 air samples taken <1 m from four different patients. In all cases, the concentration of viral RNA was low and ranged from <10 to 460 genomic copies/m 3 air. Infectious virus was not recovered from any of the PCR-positive samples analysed. Conclusions: Effective cleaning can reduce the risk of fomite (contact) transmission, but some surface types may facilitate the survival, persistence and/or dispersal of SARS-CoV-2. The presence of low or undetectable concentrations of viral RNA in the air supports current guidance on the use of specific personal protective equipment for aerosol-generating and non-aerosol-generating procedures.